Harmonics Mitigation of Industrial Motor Drives with Active Power Filters in Cement Plant-A Case Study - Y Kusumalatha; Y P Obulesh; Ch Saibabu (Institute of Advanced Engineering and Science, 2012)
With the increasing of use of power electronic controlled variable speed drives in industries, power quality distortion in electric power system has become a serious issue in recent years. In cement plants, because of presence of more number of adjustable speed electric drives, this problem is a greater concern. In this paper, the impacts of harmonic distortions due to Adjustable speed electric drives in Anjani Portland cement Ltd, Jaggayapet, Nolgonda (Dist), A.P, India is investigated. Harmonic measurements at various motor drives with the help of Fluke 434 power quality analyzer have been done to determine where a significant amount of harmonic currents or voltages are presented. From these measurements and subsequent calculations, the impact of harmonics is analyzed and found that the harmonic content of the motor drives to be minimized within the limits of international harmonic standards. In recently, active power filters gained an increased attention due to their effective harmonic reduction. In this paper an active power filter has been developed for minimization of the harmonics, which is implemented in Matlab/simulink based on real time measurement of harmonic data.DOI: http://dx.doi.org/10.11591/ijpeds.v2i1.120